Comparative analysis of competitive swimming between European and B&H swimmers in the 50m discipline - Mijanovic, M.; Grahovac, G.; Pasic, G. (Acta Kinesiologica, 2021)
The subject of the research is competitive swimming in Europe (EUR) and Bosnia and Herzegovina (B&H) from 2008 to 2018, discipline of 50m freestyle for male seniors. The problems of the research are trends, dynamics and differences between swimmers from Bosnia and Herzegovina and swimmers from Europe. The objectives of the research are: 1.To identify trends in swimming development in EUR and B&H from 2008 to 2018. 2. To determine the statistical significance of differences between EUR swimmers and B&H swimmers. 3. To evaluate the results for 2020 based on linear functions. In accordance with the set goals of the research, appropriate statistical methods and tests were applied, which enabled an exact answer to the set hypotheses and goals. The variables were being monitored in this study: 1.The time of the eight finalists 2. The time of the first three swimmers. 3. The Winner time. 4. The Record time. Based on the achieved results, it can be validly and reliably concluded that there is generally an improvement in results for EUR swimmers and B&H swimmers. It is statistically proven that there is a significant difference in the achieved results. European swimmers showed better results that were statistically significant. Linear functions i.e trends indicate that there is a small difference. There are more reasons for lagging of B&H`s swimmers behind the European swimmers. In the post-war period there are no elementary material, professional, coaching and other assumptions that enable better results either in swimming or in other sports in Bosnia and Herzegovina.